Makna Ritual dalam Aliran Musik Band Siramandalem Legion (Studi Komunitas Blackmetal di Kabupaten Boyolali) - Endarwati Kristiyani; Sri Suwartiningsih (Cakrawala Jurnal Penelitian Sosial, 2014)
One of the sub-genre of Metal Underground music is Blackmetal. The depiction of music lovers Blacmetal is always using costumes with a dark color, and a depiction of the band players also use dark-colored costume. In addition they also use Corpsepaint (facial make up in black dan white), and also use a unique and whimsical accessories. In Boyolali, metal community thereby the name of PTH (Pengging Total Hitam), which is a band with the flow Blackmetal quite popular with the audience that is Siramandalem Legion. Siramandalem Legion has uniqueness, that is they add a little ritual in their performance on stage.  The study uses descriptive-exploratory, describe and explain the ritual performed Siramandalem Legioan, of ritual before they appeared on stage, on the stage until performing on stage. Rituals that they used were some ornaments like flowers, incense, etc. Winnowing tray, and each ornament that used to have a purpose and a goal in itself. Ritual they do aim to keep local culture, that is Javanese culture. They combine musical genres Blacmetal with Javanese culture. Additionally rituals that they use as a supplement in their appearance without leaving their believe values. Rituals that they do aim to keep their relationship with God, their relationship with the environment and their relationship with each other.  Keywords : Black Metal, Siramandalem Legion, ritual